Promoting Islamic Tourism in Brunei : Through Customers Understanding Towards the Syariah Compliant Hotel Concepts - Haji Mohamed, Haji Mahmud (2014)
The demand for and supply of Islamic hospitality services has been affected positively by the increasing number of Islamic followers globally and positive tourism trends. It is assumed that the emergence of Islamic financing is one of the influences of Syariah-Compliant Hotels besides the increasing number of Arab and Muslim travellers and their high purchasing power. In the context of tourism in Brunei Darussalam, however, the report cited poor tourism infrastructure such as public transport services, limited hotel accommodations and limited aviation connectivity as the key infrastructure issues in Brunei Darussalam. Therefore this management project will try to address the need to enhance the development of Islamic Tourism in Brunei through the improvement of its current tourism infrastructure, focussing on the establishment of Syariah-Compliant Hotel using a conceptual framework developed specifically to expose the factors required for any Muslim country to be successful in today’s highly competitive hospitality market. In this respect, the author will need to test the framework with mass visitors (domestic and international) through their understanding on the importance of implementing the concept of Syariah-Compliant Hotel on the factors such as attitudes, acceptance and trust. Results have showed that the level and strength of these three factors have positive relationship with the customers understanding towards the Syariah-Compliant Hotel Concepts.